2019
DOI: 10.1002/jemt.23272
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of foliar cuticle morphology for the identification of weedy grasses

Abstract: For the robust identification of weeds of taxonomically complex families like Poaceae, scanning electron microscopy (SEM) and light microscopy (LM) are of significant implications. In this study, SEM and LM methods were used by investigating 12 Pakistani weedy grass species as an example for foliar epidermal micromorphological characters for its role in the identification of grasses species. Qualitative and quantitative foliar micromorphological variations in stomatal type, number, guard cells, subsidiary cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
(28 reference statements)
0
10
0
Order By: Relevance
“…In another study, Morgado et al (2015) reported as “small size” of caryopsis in their investigated species of Poaceae. However, caryopsis shapes along with other features such as color, surface and outer epidermal cells have reasonable taxonomic implications among taxa, as various authors have been reported (Heneidak & Khalik, 2015; Khan, Abidin, et al, 2019; Khan, Kiliç, et al, 2019). Sculpture pattern, likewise, caryopsis shape has significant diagnostic characteristics.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In another study, Morgado et al (2015) reported as “small size” of caryopsis in their investigated species of Poaceae. However, caryopsis shapes along with other features such as color, surface and outer epidermal cells have reasonable taxonomic implications among taxa, as various authors have been reported (Heneidak & Khalik, 2015; Khan, Abidin, et al, 2019; Khan, Kiliç, et al, 2019). Sculpture pattern, likewise, caryopsis shape has significant diagnostic characteristics.…”
Section: Discussionmentioning
confidence: 84%
“…But still requires more extensive studies from both taxonomic and ecological aspects. Caryopsis micromorphological using stereoscopic and scanning electron microscope has been reported as an effective means at different taxonomic levels (Gandhi, Albert, & Pandya, 2013; Jiang, Peterson, & Liu, 2011; Jordan, Jordan, & Jordan, 1983; Khan, Abidin, et al, 2017; Khan, Abidin, et al, 2019; Khan, Kiliç, et al, 2019; Khan, Ullah, Khan, Khan, & Rashid, 2017; Terrell & Peterson, 1993; Wang, Guo, & Li, 1986; Zhang, Hu, Liu, & Liu, 2014). Dhara, Susy, and Neeta (2013) used morphometric analysis of Eragrostis caryopsis for its taxonomic implication.…”
Section: Introductionmentioning
confidence: 99%
“…To clarify the taxonomic status of plants, successful anatomical studies are required to aid in the identification of different species (Evert, ). Primarily, leaf epidermal features such as size and shape of the stomatal complex, orientation and structural specialties of the epidermal cells wall and specific types of trichomes are important (Dickison, ; Khan et al, ; Khan et al, ). Although, foliar epidermal characters may be influenced by environmental conditions (Casson & Hetherington, ) but a single character is insufficient to delimit Berberis species where numerous characteristics are required for complete identification.…”
Section: Discussionmentioning
confidence: 99%
“…Different anatomical characters, such as stomata size, morphology, trichomes, epidermal cells, cell wall pattern, and so forth are of immense importance in the identification of taxonomically complex genera particularly at species level (Khan, Ahmad, Zafar, & Ullah, ; Khan et al, ; Khan et al, ; Xiang, Dong, Peng, & Liu, ). In addition, foliar epidermal characters have been used to identify species of a number of families (Ashfaq et al, ; Gul et al, ; Khan et al, ; Stefano, Papini, & Brighigna, ) while different anatomical and morphological characters are used for a long time for the identification of species, genera, and families (Li, Liao, Bai, Zhou, & Wu, ). Detailed study on the leaf epidermal anatomy and its systematic relevance within the genus Berberis is rare.…”
Section: Introductionmentioning
confidence: 99%
“…The development of nanotechnology causes growth in manufacturing technology and science as well. Microfabrication, carbon‐based chemistry, surface science, cellular biology, semiconductor science, biology, phyto anatomy, and so on are some of the science fields covered by this technology (Gul et al, 2020; Khan et al, 2019). Silver nanoparticles have evidenced to be utmost effective because of its virtuous antimicrobic activity against viruses, bacteria, and other microscopic organisms (Kale et al, 2021).…”
Section: Introductionmentioning
confidence: 99%